Evaluación técnico financiera del diseño del plan operacional de perforación radial para el pozo "A" del Campo Orito (2017)
The present work is based on the design of the Operational Plan of Radial Drilling for Pit "A" of Campo Orito, where the problem of low productivity due to the pressure loss in the deposit is presented.It begins with the description of the generalities of the Caguan Putumayo Basin, as well as the production history of Campo Orito, continuing with a technical and theoretical description of the Radial Drilling. Next, a description of the generalities of Well "A" is made, where all the information concerning the well is presented in the Interest Formations, Caballos and Villeta, besides presenting the properties of the fluid of each of them, which was necessary to carry out the simulation of the production according to the proposed operational plan. Once the above was completed, the design of the Operational Plan for Radial Drilling for Well A was carried out, consisting of the drilling of 4 lateral holes at the same depth with a length of 300 feet each one. The intention of the operation is to increase the drainage radius of the well and consequently achieve a significant increase in production, in the case of the project, based on the result of the simulation carried out, an increase of 4 times the base production of the water well.